The Effectiveness of Nutrition Education Using Audio-Visual Media on Nutrition Knowledge in Anemic Adolescents: A Scoping Review - Suni, Syahrizal Rahman; Priyatama, Aditya Nanda; Sari, Yulia (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Anemia is a nutritional problem that occurs throughout the world. Lack of nutritionalknowledge can cause anemia in adolescents. Nutrition education with audio-visual media is oneway to increase knowledge and decrease the incidence of anemia. Objective: To analyze theeffectiveness of nutrition education using audio-visual media on knowledge in anemic adolescents.Methods: This review used the PRISMA-ScR guidelines with three article search databases.Articles found were screened. Eligible articles in accordance with the inclusion criteria werereviewed. Results: A total of three articles were reviewed showing that intervention using videosignificantly increased the knowledge of adolescent girls compared to the control group (p<0.005)and was effective in preventing anemia. Conclusion: Nutrition education with audio-visual mediais effective for increasing nutritional knowledge and preventing anemia in adolescent girls. International Journal of Human and Health Sciences Vol. 08 No. 04 Oct’24 Page: 310-314